Recontextualizing Sexting and Digital Pornography as Jarimah in the Perspective of Fiqh Jinayah - Efendi, Sumardi; Mayasari, Mayasari; Masykar, Tabsyir (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2026)
The development of digital technology has given rise to the practice of sexting and digital pornography which presents moral challenges as well as legal problems in the Muslim society. This phenomenon has to do not only with private ethics, but also has an impact on the broader social order. This study aims to examine the concept, classification, and legal implications of sexting and digital pornography as jarimah in the perspective of Jinyah Fiqh. This research is a normative legal research with a qualitative approach. Data was obtained through literature studies of primary sources of Islamic law, classical and contemporary fiqh literature, and relevant scientific journals. The analysis is carried out with a conceptual approach and maqāṣid al-syarī’ah to assess the substance of the act and its impact on the public good. The results of the study showed that sexting and digital pornography did not meet the elements of hudud jarimah because they did not always involve physical intercourse as in adultery with strict evidentiary standards. However, both can be categorized as jarimah ta’zir because they contain elements of moral violations, the opening of the aurat, and the potential destruction of individual honor and public morals. Viewed from the perspective of maqāṣid al-shari’ah, the practice is contrary to the purpose of protecting honor (ḥifẓ al-’irdh), heredity (ḥifẓ al-nasl), and reason (ḥifẓ al-’aql). This research confirms that Fiqh Jinayah has normative flexibility to respond to the phenomenon of digital sexuality through the mechanism of ijtihad and the application of ta’zir, so that it remains relevant in maintaining the benefit and dignity of human beings in the digital era.